Hubungan Pengetahuan Pemerantasan Sarang Nyamuk Dan Keberadaan Jentik Aedes Sp Di Kelurahan Jambu Hilir Kecamatan Kandangan Tahun 2016 - Hardiono hardiono; Tien jubaidah; Jamilah jamilah (Politeknik Kementerian Kesehatan Banjarmasin, 2016)
Village of Jambu Hilir is one endemic Dengue Hemorrhagic Fever (DHF) in Hulu Sungai Selatan Distric . Data from Puskesmas Jambu Hilir In 2011, there were 15 cases of DHF and in 2012 there were 34 cases of dengue fever, in 2013 there were 37 cases of one person died and in 2014 to 8 cases of DHF, and in 2015 increased to 58 cases of DHF, and 1 people died, while Figures Free Flick (ABJ) 67.9% lower (<95%). This study aims to determine the relationship between knowledge about mosquito nest eradication (PSN DBD) with the presence of larvae of Aedes aegypti (Ae. Aegypti) households in the village of Jambu Hilir. Cross sectional study was conducted in 64 households, selected by simple random sampling of 236 households. Respondents are heads of households. The independent variable was public knowledge about the PSN while the dependent variable was the presence of mosquito larvae Ae. aegypti. Data were collected by interviews face advance individually housed in homes using questionnaires and observation. Data analysis was performed using univariate, bivariate and analyzed using Chi – square Test. Results showed knowledge about PSN good category 31.3%, 14.1% lacking and sufficient 54.7%. The house is positive there Aedes sp larvae 37.5% = ABJ is 62.5%. Statistically significant relationship PSN level of public knowledge about the existence of Aedes sp larvae in the home (p = 0:00). It is suggested that efforts to change behaviors that support PSN DBD is still needed. Puskesmas need to increase health promotion on the dangers of dengue and its prevention, coordination across relevant sectors and the performance of larva monitoring (jumantik) to improve the PSN behavior of households, resulting in increased morbidity, ABJ and a drop in dengue. Keywords:Knowledge PSN, free numbers larva rate, Aedes aegypti, DHF